Occupational Therapy Student Readiness for Transition to the Fieldwork Environment: A Pilot Case Study - Pamela Karp (Scholarworks @ WMU, 2020)
The classroom and the field represent diverse and unique teaching and learning environments that students are required to navigate successfully. Facilitating student success in these environments requires the efforts of educators and the students themselves. This qualitative pilot study sought to elucidate perspectives regarding student readiness from the viewpoint of occupational therapy academic and fieldwork educators. Data for the study was collected from interviews and a focus group. The results of the study revealed that academic and fieldwork educators value similar characteristics of student readiness for transition to fieldwork. However, there is a need for collaborative strategies between the academic and fieldwork settings to improve awareness of the value of theory-driven practice and to support authentic incorporation of theory into practice as part of the educative process of supervising fieldwork students.